Microbiota and its antibiotic resistance profile in avocado Guatemalan fruits (Persea nubigena var. guatemalensis) sold at retail markets of Ibarra city, northern Ecuador - Angamarca, Evelyn; Castillejo, Pablo; Tenea, Gabriela N. (Frontiers in Microbiology, 2023)
Avocados are typically sold in unsanitary conditions at the retail markets in Ecuador, which can raise the risk of microbial contamination. These microorganisms could exhibit multi-antibiotic resistance (MAR), being a serious threat concern to human health. In this study, we aimed to evaluate the microbiota and its antibiotic resistance profile in avocado Guatemalan fruits (Persea nubigena var. guatemalensis), at ripe stage: immature, firm light green (ready to eat in 4 days), peel (AFPE) and pulp (AFPU), and mature intense green (ready to eat) peel (AMPE) and pulp (AMPU), to gain baseline information on the prevalence of MAR bacteria. Based on 16S rRNA gene metagenomic analysis, over 99.78% of reads were classified as bacteria in all samples. Shannon diversity index varies from 1.22 to 2.22, with the highest bacterial population assigned to AFPE samples (1327 species). The highest microbial counts of indicator Staphylococcus spp. (STAPHY), Enterobacter spp. (ENT), and Listeria spp. (LIST), were detected in AMPE samples. Thirty percent of the selected STAPHYs, and 20.91% of Enterobacter (ENT) clones were resistant to various classes of antibiotics. The MAR index varies between 0.25 to 0.88 and was clone-, and fruit ripe stage-dependent. The results indicated that ready to eat avocados contained detectable levels of MAR bacteria, including methicillin resistant (MR)-STAPHY, which may act as a potential vector for the spread of antibiotic resistance (AR). Thus, it is crucial to set up efficient control measures and develop coordinated strategies to guarantee the microbiological quality of the food.